Investigating the Supply Chain Problems of Imputed Economic Goods in the Modern Russian Institutional Economy - Victor Konstantinov; Ildar Valiev (International Journal of Supply Chain Management, 2018)
Abstract The research was implemented with the financial support from the Russian Foundation for Basic Research (the scientific project 18-010-00636-A). It describes the supply chain problems of